(untitled) (Sociologisk Forskning, 2014)
Baby boomers and elderly care: expectations in print media about a new kind of care users The Swedish baby boomer generation – known as the forties generation – has been characterized as youthful and powerful. At present, members of this generation are entering the category of old age and in about ten years they will start reaching ages where the likelihood of encountering elderly care increases significantly. The present study reports on how this expected meeting has been discussed in Swedish newspapers. Data consisted of 481 articles during the period 1995–2012 and was analyzed through qualitative content analysis. Results show that the generation was predicted to become a new type of demanding and self-conscious care users. Claims were backed by descriptions of formative events and typical characteristics that were projected onto a future as care user. Such projections tended to portray care users of present time as passive and submissive, and partly responsible for problems associated with elderly care